Pharmacokinetics of chloroquine in Thais: plasma and red-cell concentrations following an intravenous infusion to healthy subjects and patients with Plasmodium vivax malaria. - Edwards, G; Looareesuwan, S; Davies, A; Wattanagoon, Y; Phillips, R; Warrell, D (1988)
1. Chloroquine diphosphate (15 mg base kg-1) was given by constant rate intravenous infusion to two groups of Thai subjects. Eleven were patients with malaria (10 with Plasmodium vivax and one case with Plasmodium malariae) and 10 were healthy normal volunteers. 2. Plasma and packed red-cell concentrations of chloroquine, electrocardiographic intervals, arterial blood pressure and pulse were measured at frequent intervals. 3. Peak plasma concentrations at the end of the infusion ranged from 979 to 2,900 ng ml-1 in the malaria patients. In the group of healthy subjects the range was 550-2,200 ng ml-1. Values for terminal elimination rate constant, (lambda z) plasma clearance (CL), initial volume of distribution (V1) and volume of distribution at steady state (Vss) were calculated. For the healthy subjects, mean estimates of these parameters were lambda z = 0.062 +/- 0.030 day-1, CL = 597 +/- 238 ml min-1, V1 = 0.66 +/- 0.71 l kg-1 and Vss = 132 +/- 50 l.kg-1 For the group of malaria patients, the corresponding values were lambda z = 0.055 +/- 0.032 day-1, CL = 535 +/- 246 ml min-1, V1 = 0.74 +/- 0.75 l kg-1 and Vss = 136 +/- 64 l kg-1 There was no statistically significant difference in the estimates for any parameter between groups (P less than or equal to 0.05). 4. Chloroquine concentrations in packed red blood cells consistently exceeded those in plasma and showed no consistent change with time throughout the period of study in either group. The median value for the red cell to plasma ratio was between 3 and 4 in each group.(ABSTRACT TRUNCATED AT 250 WORDS)